Modifikasi Pati Sagu Dengan Metode Asetilasi Untuk Peningkatan Sifat Tensile Bioplastik - Yoga Deswan Suwary; Yelmida Yelmida; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Bioplastics are an alternative material to replace conventional plastic packaging so as not to pollute the environment. One method of modifying bioplastics is the acetylation method which is a modified starch method obtained from reacting starch with hydroxyl groups to produce hemiacetal and aldehyde. This study aims to make modified bioplastics with better tensile strength than ordinary bioplastics. The analysis performed was FTIR test, substitution degree test, and mechanical properties of tensile strength. The best results from each test are the value obtained by the value of the substitution degree 0,992, FTIR at the vibration for the wavelength range 1633 - 1645 cm-1, the tensile strength value of 1,893 MPa bioplastically penetrated the decay results of the methylated starch and 12 % filler content b / b and 10 % plasticizers b / b.Keywords : acetylation, bioplastic, acetylated starch, acetylated bioplastic